2015
DOI: 10.1002/hyp.10613
|View full text |Cite
|
Sign up to set email alerts
|

Effect of succession gaps on the understory water-holding capacity in an over-mature alpine forest at the upper reaches of the Yangtze River

Abstract: Abstract:The water-holding capacity (WHC) of the understory in the headwater regions of major rivers plays an important role in both the capacity of the forest water reservoir and water quality and quantity in the butted rivers. Although forest gaps could regulate water-holding patterns in the understory by redistributing coarse woody debris (CWD), fine woody debris (FWD), non-woody debris (NWD) and understory vegetation, little information is available on the effects of forest gaps on understory WHC. Therefor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…Methodological limitations withstanding, the S U estimates in this study fit within the range of water storage capacities of other herbaceous plants synthesized by Breuer et al (2003). This synthesis is focused on the leaves of herbaceous plants (alongside other plant types) (Breuer et al, 2003), but less research has estimated the stem component (or reported a total including the stem component) of the water storage capacity for short vegetation (Bradley et al, 2003;Wang et al, 2016;Wohlfahrt et al, 2006;Yu et al, 2012). The stems of herbaceous plants, even thick smooth stems (> 1 cm in diameter) can store nearly 0.5 mm, e.g., Taraxacum officinale (dandelion) (Wohlfahrt et al, 2006).…”
Section: Overstory Throughfall Partitioning By Dogfennelmentioning
confidence: 76%
“…Methodological limitations withstanding, the S U estimates in this study fit within the range of water storage capacities of other herbaceous plants synthesized by Breuer et al (2003). This synthesis is focused on the leaves of herbaceous plants (alongside other plant types) (Breuer et al, 2003), but less research has estimated the stem component (or reported a total including the stem component) of the water storage capacity for short vegetation (Bradley et al, 2003;Wang et al, 2016;Wohlfahrt et al, 2006;Yu et al, 2012). The stems of herbaceous plants, even thick smooth stems (> 1 cm in diameter) can store nearly 0.5 mm, e.g., Taraxacum officinale (dandelion) (Wohlfahrt et al, 2006).…”
Section: Overstory Throughfall Partitioning By Dogfennelmentioning
confidence: 76%
“…The alpine forest located in the upper reaches of the Yangtze River and the eastern Qinghai-Tibet Plateau plays important roles in holding fresh water, sequestering carbon and indicating climate change [ 19 , 20 ]. Previous studies have indicated that fallen logs with different decay classes account for 53.00 t·ha -1 in the primary Minjiang fir ( Abies faxoniana ) forest ecosystem [ 21 ] and play crucial roles in nurturing biodiversity, maintaining site productivity and holding water [ 22 ]. However, the changes that occur in the microbial community in different decay classes of fallen logs with critical periods remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Faunal abundance varies between seasons with changes in temperature and rainfall [20,21]; moreover, hydrological leaching that contributes to DOC and TDN release normally occurs during the growing season [22,23]. Whether the faunal effect interacts with this process is unclear.…”
Section: Introductionmentioning
confidence: 99%